At the origins of the political discourse of the 5-Star Movement (M5S): Internet, direct democracy and the "future of the past". Issue 1 (3rd April 2018) - Musso, Marta; Maccaferri, Marzia
ABSTRACT: The 5-star Movement (Movimento 5 Stelle, M5S) is a political party in Italy operating almost exclusively online. It was officially established as a political movement in 2009, and quickly became the second most important political force in Italy. Unlike traditional political parties, the Movement operates almost exclusively online, without any headquarters and non-digital types of communication (until recently, candidates were forbidden to give interviews on TV or to the press); Beppe Grillo's blog (www.beppegrillo.it ), used as an aggregator by early activists, is now the main "spokesperson" of the party; it is not just a tool of communication that replaces traditional party newspapers, but an integral part of the party's life and of its history. This research will first give an overview of the relation between the 5-Star Movement and the World Wide Web, particularly the blog. In second instance, through a deeper analysis of the blog posts from 2008 until the end of 2017, the paper will try to determine what is the main political discourse underlying the M5S on two key "ideological issues": migration and the European Union, and how the party's positions have evolved over the years.